Low immunoglobulin E flags two distinct types of immune dysregulation. (11th January 2017) - Elkuch, M.; Greiff, V.; Berger, C. T.; Bouchenaki, M.; Daikeler, T.; Bircher, A.; Navarini, A. A.; Heijnen, I.; Recher, M.
Summary: During the last two decades, hyper‐immunoglobulin (Ig)E syndromes have been characterized clinically and molecularly in patients with genetically determined primary immunodeficiencies. However, the detection of low IgE levels, defined here as below detection limit in the routine clinical immunology laboratory, has received little attention. We analysed the association of serum IgA, IgM and IgG levels (including IgG subclasses) with low, normal or high serum IgE levels in patients evaluated in a single‐centre out‐patient immunodeficiency and allergy clinic. The correlation of serum IgE levels with IgG subclasses depended on the clinical phenotype. In patients with immunodeficiencies, IgE correlated with IgG2 and IgG4 but not with IgG3. In contrast, in patients referred for signs of allergy, IgE correlated with IgG3 but not with IgG2. A low IgE result was associated with low IgG3 and IgG4 in allergy referrals, while immunodeficiency referrals with a low IgE result had significantly lower IgG1, IgG2 and IgG4 levels. Hierarchical clustering of non‐IgE immunoglobulin profiles (IgM, IgA, IgG, IgG1–4) validated that non‐IgE immunoglobulin levels predict the clinic referral, i.e. phenotype, of low‐IgE patients. These results suggesto guide the clinical management of patients with low serum IgE levels. Abstract : Patients with low serum IgE have not been characterized in detail so far. In this article we show that this patient group consists of a least two clinically and immunologically distinct subgroups. One patient subgroup has the diagnosis of antibody deficiency, while the other subgroup has symptoms of allergic disease.